1993
DOI: 10.1002/jmr.300060206
|View full text |Cite
|
Sign up to set email alerts
|

Peptide vaccines incorporating a ‘promiscuous’ T‐cell epitope bypass certain haplotype restricted immune responses and provide broad spectrum immunogenicity

Abstract: An ideal peptide vaccine should contain both B- and T-cell epitopes. Recognition of antigen by B cells is highly dependent on the three-dimensional conformation of the antigen whereas T cells recognize antigen only after it has been processed to release a peptide fragment which is bound to the major histocompatibility complex (MHC) class II molecule. However, T cells provide 'help' to B cells displaying the same processed, MHC-restricted form of the antigen, demonstrating that the T-cell response to a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 57 publications
0
50
1
Order By: Relevance
“…We have demonstrated in the past that this chimeric peptide vaccine strategy can elicit robust Ab responses in multiple strains of mice and outbred animals (24,57,84,85). In the present study we evaluated four novel HER-2 B cell epitopes to assess the possibility of developing a multiepitope peptide vaccine that could elicit a superior antitumor response.…”
Section: Discussionmentioning
confidence: 98%
“…We have demonstrated in the past that this chimeric peptide vaccine strategy can elicit robust Ab responses in multiple strains of mice and outbred animals (24,57,84,85). In the present study we evaluated four novel HER-2 B cell epitopes to assess the possibility of developing a multiepitope peptide vaccine that could elicit a superior antitumor response.…”
Section: Discussionmentioning
confidence: 98%
“…28 We addressed the third hurdle by engineering chimeric peptide constructs by incorporating a 'promiscuous' T-cell epitope, which can bind multiple haplotypes with the appropriate B-cell epitope. 29 We surveyed several "promiscuous" T cell-epitope and found that the measle virus fusion (MVF) protein (epitope sequence 298-302) to be the most efficacious. Another T-helper epitope peptide P30 from tetanus toxoid was used as the immunostimulant in MUC1 glycopeptide antitumor vaccines and apparently it also acts as a builtin adjuvant P30-conjugated glycopeptide vaccines.…”
Section: Unique Peptide B-cell Epitope Vaccinesmentioning
confidence: 99%
“…[36][37][38][39][40][41] We begin by predicting B-cell epitopes followed by molecular modeling to recapitulate the native structure of the tumor antigen. 23,29,42 This is followed by the design of the chimeric vaccine by incorporating a "promiscuous" T cell epitope for the production of antipeptide-antibodies in animals. [25][26][27]43 Stable peptide mimics are designed, synthesized and tested in a series of in vitro assays in different human cancer cell lines to corroborate efficacy with antipeptide antibodies.…”
Section: Enabling Chimeric Peptide B-cell Vaccine Strategymentioning
confidence: 99%
“…A synthetic peptide antigen, C-TT2-CTP35, consisting of a B-cell epitope from CTP (residues 111-145) [7] and a T-cell epitope from tetanus toxoid (TT) (residues 830-844, designated as TT2) [8,9] has been shown to elicit antibody responses comparable to those induced by the same CTP fragment conjugated to diphtheria toxoid [10]. As a "promiscuous" or universal T-cell epitope, TT2 provides advantage of not being MHC-restricted and thus broadly reactive in multiple haplotypes, as compared with TT or diphtheria toxoid, which often have been used as carriers for hCG vaccines to provide the T-cell helper effect [8,9]. However, strong adjuvant oily vehicles such as a combination of squalene, surface active agents, and/or bacteria surface component analogues were necessary to induce strong immune responses to C-TT2-CTP35 -a recurring problem for poorly immunogenic peptide vaccines [3,10].…”
Section: Introductionmentioning
confidence: 99%